Dipeptidyl peptidase IV inhibitor improves the salivary gland histology of spontaneously diabetic mice - Da Silva Faria, Ana Luyza Domingues; Dias, Marco Antônio; Leme, Vinicius Barichelo; Mayoral, Éber Emanuel; Da Silva, Rodrigo Eduardo; Mâncio, Rafael Dias; Ferreira Junior, Rui Seabra [UNESP]; Caldeira, Eduardo José (Elsevier, 2013)
Objectives: The incretin-based therapy might be effective in patients possessing certain levels of preserved pancreatic beta-cells. However, doubts still exist regarding the efficacy of this atment in the recovery of tissues damaged by type 1 diabetes. Thus, the objective of this study was to evaluate the treatment with MK0431 in salivary glands of spontaneously diabetic mice, focusing mainly on the possible therapeutic and hypoglycaemic effects of this dipeptidyl peptidase IV inhibitor in the recovery of these salivary tissues. Methods and results: Twenty mice were divided into two groups of 10 animals each: group I (NOD diabetic/untreated) and group II (NOD diabetic MK0431/treated). The group II was treated during 4 weeks with MK0431 mixed in the food. The group I was maintained in the same way without receiving, however, any treatment. Glucose levels were monitored during treatment and salivary glands samples were collected at the end of treatment for the histological examination under both transmitted and polarized light microscopy. High glucose levels were observed in untreated animals, while in animals with treatment, reduction of these levels was observed. Tissue restructuring was also observed in animals submitted to therapy with MK0431, mainly in relation to the attempt to extracellular matrix reorganization. Conclusions: According to results, the treatment with this dipeptidyl peptidase IV inhibitor contributed to the general homeostasis of the organism and to the reestablishment of both epithelial and stromal compartments which were damaged by the hyperglycaemic condition, demonstrating that the incretin-based therapy may be an important complementary treatment for the type 1 diabetic condition. © 2012 Elsevier Ltd.
Keywords: Complementary therapies; Diabetes mellitus; Salivary glands; Animalia; Mus